Power Factor Control of Matrix Converter Based Induction Motor Drive - Keream, Settar S.; Abdalla, Ahmed N.; Mohd Razali, Daud; Ruzlaini, Ghoni; Al Mashhadany, Youssif (Canadian Centerof Science and Education, 2015)
The Induction Motors utilizing Matrix Converters with Direct Torque Control (DTC) is a great responsibility for motor control scheme with expeditious torque and flux replications. This paper shwed a new power factor control along with the existing DTC matrix converter induction motor drive. The core benefits of the DTC matrix converter are improved with those of the power factor technique, the required voltage vectors is producing under 0.86 input power factor operations. The implementation of this kind of controller is done by using the TMS320F28335. The results validate the good quality and robustness in the proposed system dynamic response and reduction in the transient motor ripple torque.